Defining durum wheat ideotypes adapted to Mediterranean environments through remote sensing traits - Gracia-Romero, Adrian; Vatter, Thomas; Kefauver, Shawn C.; Rezzouk, Fatima Zahra; Segarra, Joel; Nieto-Taladriz, María Teresa; Aparicio, Nieves; Araus, José Luis (Frontiers in Plant Science, 2023)
An acceleration of the genetic advances of durum wheat, as a major crop for the Mediterranean region, is required, but phenotyping still represents a bottleneck for breeding. This study aims to define durum wheat ideotypes for Mediterranean conditions by selecting the most suitable phenotypic remote sensing traits, among different ones informing on characteristics related with leaf pigments/photosynthetic status, crop water status and crop growth/green biomass. A set of 24 post green revolution durum wheat cultivars were assessed in a wide set of 19 environments, accounted as the specific combinations of a range of latitudes in Spain, under different management conditions (water regimes and planting dates), through three consecutive years. Thus, RGB and multispectral derived vegetation indices and canopy temperature were evaluated at anthesis and grain filling. The potential of the assessed remote sensing parameters alone and all combined as grain yield (GY) predictors was evaluated through random forest regression models performed for each environment and phenological stage. Biomass and plot greenness indicators consistently proved to be reliable GY predictors in all of the environments tested for both phenological stages. For the lowest-yielding environment, the contribution of water status measurements was higher during anthesis, while for the highest-yielding environments, better predictions were reported during grain filling. Remote sensing traits measured during the grain filling and informing on pigment content and photosynthetic capacity were highlighted under the environments with warmer conditions, as the late-planting treatments. Overall, canopy greenness indicators were reported as the highest correlated traits for most of the environments and regardless the phenological moment assessed. The addition of carbon isotope composition of mature kernels was attempted to increase the accuracies, but only a few were slightly benefited, as differences in water status among cultivars were already accounted by the measurement of canopy temperature.